Analysis and design of hammerhead bridge pier using a strut and tie method - Ahyat, Abdul Kadir (2005)
The main advantages of truss model are their transparency and adaptability to arbitrary geometric and loading configuration. In strut-and-tie modeling, the internal stresses are transferred through a truss mechanism. The tensile ties and compressive struts serve as truss members connected by nodal zones. The advantages have been thrust into the back ground by several recent developments of design equations based on truss models, The present study is focus on developing a uniform design procedure for applying the strut-and-tie modeling method to hammerhead pier. A study was conducted using hammerhead piers that were previously designed using the strength method specified by code. This structure was completed and had put into service. During the inspection, cracks were observed on the piers. The scope of this study is to highlight the application of a newer generation strut-and-tie model, which is not practice at the time of the original design. Depth to span ratios varies from 1.5 to 2.11 and the girders are transferring loads very close to the support edge, making these hammerheads ideals candidates for strut-and-tie application. This study only focus on comparison the reinforcement detail drawing produce previously designed using the strength method, and reinforcing requirement using strut-and-tie model. Based on the design studies, a well-defined procedure for designing a hammerhead pier utilizing the strut-and-tie model was established that may be used by bridge engineers. There could be numerous reasons for the crack to develop. Shrinkage, stress concentration or some erection condition may be a few of them.